2019
DOI: 10.1111/evo.13788
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sex genetic covariances limit the evolvability of wing‐shape within and among species of Drosophila

Abstract: The independent evolution of males and females is potentially constrained by both sexes inheriting the same alleles from their parents. This genetic constraint can limit the evolvability of complex traits; however, there are few studies of multivariate evolution that incorporate cross‐sex genetic covariances in their predictions. Drosophila wing‐shape has emerged as a model high‐dimensional phenotype; wing‐shape is highly evolvable in contemporary populations, and yet perplexingly stable across phylogenetic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 89 publications
4
34
1
Order By: Relevance
“…For this matrix, the predicted average indirect response of dimorphism to random concordant vectors was about 20% higher than the response to random antagonistic vectors. The wing shape G mf matrix (Sztepanacz and Houle 2019), in contrast, had a higher than average r MF value of 0.92, and as predicted by our theory, the predicted average indirect response of dimorphism to random concordant vectors was 50% higher than the response to random antagonistic vectors. In contrast, we also made predictions for two G mf matrices for CHC expression (Ingleby et al 2014) that had very low average r MF values of 0.24 and 0.04.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…For this matrix, the predicted average indirect response of dimorphism to random concordant vectors was about 20% higher than the response to random antagonistic vectors. The wing shape G mf matrix (Sztepanacz and Houle 2019), in contrast, had a higher than average r MF value of 0.92, and as predicted by our theory, the predicted average indirect response of dimorphism to random concordant vectors was 50% higher than the response to random antagonistic vectors. In contrast, we also made predictions for two G mf matrices for CHC expression (Ingleby et al 2014) that had very low average r MF values of 0.24 and 0.04.…”
Section: Resultssupporting
confidence: 77%
“…Houle and Cheng (2020a) estimated a broad-sense G matrix from these data, defining traits on the basis of a principal component analysis of relatively unbiased genes, resulting in k p 4 linear combinations of expression traits. Second, we used the G matrix estimated by Sztepanacz and Houle (2019) from k p 20 wing shape traits gathered by Mezey and Houle (2005). Finally, we used two G matrices for cuticular hydrocarbon (CHC) expression that Ingleby et al (2014) estimated in a subset of the genotypes first studied by Innocenti and Morrow (2010).…”
Section: Application To G Matrix Estimatesmentioning
confidence: 99%
“…In a recent article, we showed that multivariate cross‐sex genetic covariances ( B ) can significantly bias the predicted responses to selection in Drosophila melanogaster wing shape (Sztepanacz and Houle 2019). Manipulative experiments have also shown this to be the case.…”
Section: Figurementioning
confidence: 99%
“…However, explicit tests for association between estimated male frequency and locomotion bias do show suggestive effects on locomotion bias and one hermaphrodite transition rate (and male frequency is positively correlated with male activity itself; see Materials and Methods 5.2.3). As discussed by Sztepanacz and Houle (2019), antagonistic selection could be constrained when genetic correlations between sexes are strong, and we cannot rule out that unmeasured evolution of sexual interactions contributes to G -matrix evolution. Despite this caveat, given the laboriousness of obtaining large quantities of males from each of the inbred lines (Teotónio et al, 2006), and that males and hermaphrodites showed qualitatively similar phenotypic evolution, for the remaining we focus on the evolution of hermaphrodite locomotion bias.…”
Section: Resultsmentioning
confidence: 98%